Extension of a finite strip bonded to a rigid support - Gecit, M.R.; Turgut, A. (Springer-Verlag, 1988)
This paper considers the elastostatic plane problem of a finite strip. One end of the strip is perfectly bonded to a rigid support while the other is under the action of a uniform tensile load. Solution for the finite strip is obtained by considering an infinite strip containing a transverse rigid inclusion at the middle and two symmetrically located transverse cracks. The distance between the two cracks is equal to twice the length of the finite strip. In the limiting case when the rigid inclusion and the cracks approach the sides of the infinite strip, the region between one crack and the rigid inclusion becomes equivalent to the finite strip. Formulation of the problem is reduced to a system of three singular integral equations using the Fourier transforms. Numerical results for stresses and stress intensity factors are given in graphical form. © 1988 Springer-Verlag.